Performance, blood biochemistry, carcass fatty acids, antioxidant status, and HSP70 gene expressions in Japanese quails reared under high stocking density: the effects of grape seed powder and meal - Sur, Aslihan; Zengin, Muhittin; Bacaksiz, Oguz Koray; Gokce, Zehra; Yilmaz, Okkes; Gurses, Murad; Esen, Selim (Springer, 2023)
Japanese quails reared under high stocking density (SD) were evaluated for the effects of grape seed powder (GSP) and meal (GSM) supplementation on performance, blood biochemistry, thigh and breast muscle fatty acids, antioxidant status, and HSP70 gene expression. We randomly assigned 288 (15-day-old) quail chicks to six treatment groups in a factorial design (2 x 3) with four replicates, involving two density levels [160 cm(2)/bird (LD) and 80 cm(2)/bird (HD)] and three feed forms (FFs) [no supplementation, grape seed powder (3% GSP), grape seed meal (3% GSM)]. SD had a significant effect on live weight, but not on weekly feed intake, daily weight gain, and feed conversion ratio. Serum creatinine and aspartate aminotransferase levels were significantly affected by FF and SD x FF (p < 0.05). A high SD reduced the n-3/n-6 ratio of breast muscle and a significant interaction was found between FF (p < 0.001). The SD x FF interaction reduced the sigma n-6 ratio in HDM's thigh muscle, whereas in LDM, the ratio increased (p < 0.01). At high SD, neither GSP nor GSM reduced biological markers of oxidative stress (p > 0.05). Compared to GSP, GSM had higher efficacy at reducing HSP70 levels related to high SD levels. Despite this, at high SD, a diet containing 3% of GSP and GSM was not effective in overcoming oxidative stress. Therefore, more studies using different doses of GSM and GSP in quail diets would be beneficial.
Keywords: Stocking density; Quail; Grape seed meal; Grape seed powder; Blood biochemistry; Heat shock protein 70